A collaborative model for leadership education in high-potential university women students - Pilar Laguna-Sánchez; Mónica Segovia-Pérez; Concepción de la Fuente-Cabrero; Ana M. Vargas-Pérez (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Society recognizes the need to progress towards equal opportunities for leadership at all levels of political and economic decision-making for women and requires that companies work to reach that goal. Nevertheless, leadership education should begin in the educational stages. This research presents a collaborative model of leadership education for high-potential female undergraduate students carried out at the university level between 2017 and 2020, with 75 students. To be successful at improving student leadership skills, self-esteem, self-confidence, and personal inner transformation, this women's leadership development program was based on four lines of innovation: (a) attracting external stakeholders to develop training jointly; (b) making an open program with multidisciplinary students in social sciences and STEM subjects tailored to the professional environment; (c) measuring the learning with all the participants: trainers, directors, managers, program staff and students, using a 360-degree evaluation; and (d) designing an ongoing research process to incorporate improvements from multiple stakeholder perspectives. A multi-source program assessment was used. The results not only show a positive impact on the students' acquisition of leadership skills but also, on the increase in self-confidence and ambition. The study provides a pioneering model for women's leadership education that could be used in other similar programs.
Keywords: 650; open innovation; leadership skills training; self-confidence; female learning; female barriers